Modelling of slag flow and prediction of corrosion state of refractory bricks in an entrained-flow gasifier. (1st September 2020) - Lin, Kuo; Shen, Zhongjie; Liang, Qinfeng; Xu, Jianliang; Liu, Haifeng
Highlights: The effect of operation conditions to refractory brick corrosion was discussed. Different corrosion models of refractory brick were proposed. The brick corrosion rate was well correlated with the 1/2 power of the slag shear rate. Abstract: The corrosion rate of refractory brick is a key factor for long-term and stable operation of a gasifier. In situ measurement of refractory brick corrosion was always a challenging topic due to the extreme temperature and pressure in the gasifier. In this paper, numerical simulations were adopted to accurately predict the corrosion depth of the refractory brick. Models for slag flow and refractory brick heat transfer were built, and various models of refractory brick corrosion rate were derived in detail. Heat transfer and brick corrosion models were validated with available industry data and the prediction accuracies of the different models were compared and discussed. Results showed that the external diffusion model could accurately predict the corrosion state, and the correlation coefficient with industry data was 0.998. The slag shear rate on the surface of the refractory brick was a key control parameter for corrosion, especially for a top single-burner down-flow gasifier.